2007
DOI: 10.1086/522091
|View full text |Cite
|
Sign up to set email alerts
|

Individual Size Variation and Population Stability in a Seasonal Environment: A Discrete‐Time Model and Its Calibration Using Grasshoppers

Abstract: Much recent literature is concerned with how variation among individuals (e.g., variability in their traits and fates) translates into higher-level (i.e., population and community) dynamics. Although several theoretical frameworks have been devised to deal with the effects of individual variation on population dynamics, there are very few reports of empirically based estimates of the sign and magnitude of these effects. Here we describe an analytical model for sizedependent, seasonal life cycles and evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…Although ecologists have long been interested in the role of intraspecific variation for population and community dynamics (Bolnick et al 2011), most studies have been theoretical or focused on particular populations (e.g., Filin and Ovadia 2007;Vindenes et al 2008;González-Suárez et al 2011). This study takes a different approach to this question, using global comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ecologists have long been interested in the role of intraspecific variation for population and community dynamics (Bolnick et al 2011), most studies have been theoretical or focused on particular populations (e.g., Filin and Ovadia 2007;Vindenes et al 2008;González-Suárez et al 2011). This study takes a different approach to this question, using global comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The population biology literature has shown that variation among individuals and/or populations within a species can influence population dynamics (Filin and Ovadia 2007;González-Suárez et al 2011). The plant invasion biology literature has paid considerable attention to one type of variation formulating the phenotypic plasticity hypothesis, which posits that phenotypically plastic species are better able to establish and spread in novel environments (Richards et al 2006;Davidson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Begon et al (2006) reported that the individuals that composed a species population are not identical and may vary, sometimes very slightly, in size, development rate and/or in response to temperature. Studies point out that the variation in body size is a property of natural populations and has important ramifications for the understanding of the dynamics and stability of ecological systems (Filin and Ovadia, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the morphometric characteristics of insects has been very useful in population studies, in terms of communities, and is used for the identification of nymph stages, features of sexual dimorphism (Zolessi, 1956;Turk and Barrera, 1976;Cepeda-Pizarro et al, 2003;Domenico, 2005;Cherril, 2005;Franceschini et al, 2005;Ferreira et al, 2006;Seffrin et al, 2006), life history and evolution with host plants (Klingenberg and Spence, 1997;Ahnesjö and Forsman, 2003;Adis et al, 2008), as well as ecological studies of populations and communities (Dirsh, 1953;Roonwal, 1981;Filin and Ovadia 2007;Pires et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Body size affects behaviour and performance of individuals in most animal species (Filin and Ovadia 2007). This could be true of insects that vary greatly in body size, especially in the same gender.…”
Section: Introductionmentioning
confidence: 99%